Evaluating the Implementation of Isak 35 in the Financial Reporting Practices of the Awwal Fathul Mubien Grand Mosque, Manado City - Jan, Radlyah Hasan; Wokas, Heince Ruddy Nicky (Kunuz: Journal of Islamic Banking and Finance, 2025)
This study aims to evaluate the applicability of ISAK 35 to the financial reporting practices of the Great Awwal Fathul Mubien Mosque in Manado City and to reconstruct its financial statements in accordance with non-profit reporting standards. Using a qualitative case-study approach, this research employed observation, in-depth interviews with key financial officers, and document analysis. The data were analyzed using the Miles and Huberman interactive model through stages of reduction, display, and conclusion drawing. The findings reveal significant gaps between the mosque’s existing cash-based practices and the requirements of ISAK 35. The current system records only cash inflows and outflows, resulting in the absence of core components such as the statement of financial position, comprehensive income, changes in net assets, cash flows, and notes to the financial statements. The reconstruction process demonstrates the presence of substantial invisible assets—primarily waqf land and heritage buildings valued at approximately IDR 17.3 billion—that had never been formally recognized. The application of ISAK 35 also uncovers the mosque’s actual operational surplus and net asset position, provides clearer distinctions between restricted and unrestricted funds, and highlights structural and governance issues that hinder proper reporting. The study concludes that the mosque’s existing reporting system provides social accountability but fails to meet institutional accountability required for an entity managing significant public assets. Despite the voluntary nature of ISAK 35 adoption, the mosque’s historical and financial prominence creates a higher moral obligation to transition toward standardized reporting.